PENGGUNAAN UNGKAPAN PERMOHONAN TE KURE OLEH PENUTUR WANITA DALAM BAHASA JEPANG - Winengsih, Winengsih; Aibonotika, Arza; Nimashita, Hana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study explains about the purpose of request phrase te kure by women in Japanese language conversation dialogue. The aims of this study are to analyze what are the social factors and social dimensions influence the use of te kure request used by women. This research’s data are dialogues of Japanese language conversation using the expression of te kure request contained from two dramas entitled Majisuka Gakuen season 2 and Majisuka Gakuen season 3. The theory used in the analysis are theory of request phrase te kure from Isao Iori (2001) and social factor theory and social dimension from Janet Holmes (2001), they are applied to analysis with qualitative descriptive approach. The result of this study indicated that from the four components of social factors, the most influentian factor in the use of request phrase te kure based on the research analysis is participants, whereas the four components of social dimensions that sufficiently affect the use of te kure request is status scale. Both of these factors will equip each other to establish the use of request phrase te kure by women.Key Words: irai, te kure, social factors, social dimensions